Disabling XAuthors, Disordering TextsX: Deconstructing Disability and Identity in ChangingX Times*. (June 2016) - Blyth, C.; Chapman, R.; Stronach, I.
Drawing on Badiou's writing, we develop new insights on some central notions of the discourse on "disability." We offer eight agonistic, intersecting trajectories addressing these concepts. Drawing on authorial voices, we criticize the grammatical and rhetorical maneuvers we have previously undertaken as we represent ourselves aiming for forms of participatory engagement, thus offering both critique and self-critique. Previous poststructuralist accounts in this area have drawn on "philosophers of difference, " but mainly Deleuze and Guattari. This piece offers innovation in harnessing aspects of Badiou's thinking to issues surrounding "discourses of disability" and notions of the research "self" in its various "impersonations."